Baseline results of the NeuroNEXT spinal muscular atrophy infant biomarker study. Issue 2 (21st January 2016) - Kolb, Stephen J.; Coffey, Christopher S.; Yankey, Jon W.; Krosschell, Kristin; Arnold, W. David; Rutkove, Seward B.; Swoboda, Kathryn J.; Reyna, Sandra P.; Sakonju, Ai; Darras, Basil T.; Shell, Richard; Kuntz, Nancy; et al.
Abstract: Objective: This study prospectively assessed putative promising biomarkers for use in assessing infants with spinal muscular atrophy (SMA). Methods: This prospective, multi‐center natural history study targeted the enrollment of SMA infants and healthy control infants less than 6 months of age. Recruitment occurred at 14 centers within the NINDS National Network for Excellence in Neuroscience Clinical Trials (NeuroNEXT) Network. Infant motor function scales and putative electrophysiological, protein and molecular biomarkers were assessed at baseline and subsequent visits. Results: Enrollment began November, 2012 and ended September, 2014 with 26 SMA infants and 27 healthy infants enrolled. Baseline demographic characteristics of the SMA and control infant cohorts aligned well. Motor function as assessed by the Test for Infant Motor Performance Items (TIMPSI) and the Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP‐INTEND) revealed significant differences between the SMA and control infants at baseline. Ulnar compound muscle action potential amplitude (CMAP) in SMA infants (1.4 ± 2.2 mV) was significantly reduced compared to controls (5.5 ± 2.0 mV). Electrical impedance myography (EIM) high‐frequency reactance slope (Ohms/MHz) was significantly higher in SMA infants than controls SMA infants had lower survival motor neuron (SMN) mRNA levels in blood than controls, and several serum protein analytes were altered between cohorts. Interpretation: By the time infants were recruited and presented for the baseline visit, SMA infants had reduced motor function compared to controls. Ulnar CMAP, EIM, blood SMN mRNA levels, and serum protein analytes were able to distinguish between cohorts at the enrollment visit.